Communicating towards resiliency: identifying the barriers and social constraints related to grazing best management practices in Kansas and Oklahoma - King, Audrey E. H. (Kansas State University, 2016)
Kansas and Oklahoma were in the top five cattle producing states in the United States. Beef cattle producers across Kansas and Oklahoma had access to best management practices (BMPs) for proper grazing land management, but were still underutilizing these practices. This study sought to understand why producers did not adopt grazing BMPs suggested by Extension professionals and to identify opportunities to improve communication and adoption. Under the postulates of elaboration likelihood model (ELM), if BMPs were communicated to producers in a way that persuaded them to adopt BMPs, the resiliency of the entire beef cattle grazing system, would increase. This study was guided by community-based social marketing (CBSM) and elaboration likelihood model (ELM). Semi-structured qualitative interviews were conducted with 43 producers in north central Oklahoma and south central Kansas during the summer of 2015. Initial participants were recruited using a purposive sampling method through Extension contacts with a snowball sample after initial participants were identified. Interviews were transcribed by a professional transcription service and analyzed using Glaser’s constant comparative method. Producers in the study were aware of BMPs like rotational grazing, prescribed burning, and the usage of alternative forages. The major themes discovered in this study include Producers had varying definitions of both rotational grazing and cover crops; Producers used each other, Extension and university materials and personnel as information sources; Practices producers used were determined by visual observations and past experiences. Barriers and social constrains to the adoption of BMPs that were discovered included: water availability and quality, land leases, time and labor, land lords, generational gaps, and a lack of skilled employees. Producers saw the benefits of burning practices and rotational grazing. Another major theme was drought tested the resiliency of producer’s operations. This study offers several recommendations for Extension professionals and research. The way that Extension agents were communicating BMPs should be researched and analyzed. The implementation of CBSM and ELM by Extension professionals could increase the adoption of BMPs in grazing systems. A major implication of this study was the need for Extension to more openly communicate with producers rather than just exchange information.
Keywords: best management practices; social constraints; community based social marketing; elaboration likelihood model; communicationgrazing